Pregnancy and Acute Lymphoblastic Leukemia: A Case Series and Review of Literature - Sukrita Bhattacharjee; Shouriyo Ghosh; Siddhartha Sankar Ray; Sambit Samanta; Nilanjan Sinha; Sandeep Saha; Maitreyee Bhattacharyya (Indian Journal of Medical and Paediatric Oncology)
Acute lymphoblastic leukemia (ALL) diagnosed during pregnancy is rare and causes ethical and therapeutic challenges. We performed a retrospective search of ALL patients (n = 202) treated at our institution from 2015 to 2020 and found five patients diagnosed during pregnancy. In this report, we discuss the individual patients in detail and the challenges faced during their treatment. The use of established lymphoblastic leukemia treatment protocols and the modifications made therein to prevent untoward chemotherapy-related toxicities to the fetus are discussed in this study. We report the second use of rasburicase during pregnancy in literature with favorable maternal and fetal outcomes. We also present an extensive literature review of 41 cases of ALL in pregnancy previously reported. It is important to note that there is a dearth of guidelines for the treatment of these complex situations, and although certain general principles can be established, an individualized approach is needed in most cases of leukemia diagnosed during pregnancy.